Polyp and tumor microenvironment reprogramming in colorectal cancer: insights from mucosal bacteriome and metabolite crosstalk - Hadi Feizi; Hossein Samadi Kafil; Andrey Plotnikov; Vladimir Kataev; Alexander Balkin; Ekaterina Filonchikova; Mohammad Ahangarzadeh Rezaee; Reza Ghotaslou; Mohammad Sadrkabir; Hiva Kadkhoda; Fadhil S. Kamounah; Sergei Nikitin (Annals of Clinical Microbiology and Antimicrobials)
Abstract Background Highly frequent colorectal cancer (CRC) is predicted to have 3.2 million novel cases by 2040. Tumor microenvironment (TME) bacteriome and metabolites are proposed to be involved in CRC development. In this regard, we aimed to investigate the bacteriome and metabolites of healthy, adenomatous polyp, and CRC tissues. Methods Sixty samples including healthy (H), adenomatous polyps (AP), adenomatous polyps-adjacent (APA), cancer tumor (CT), and cancer tumor-adjacent (CA) tissues were collected and analyzed by 16 S rRNA sequencing and 1H NMR spectroscopy. Results Our results revealed that the bacteriome and metabolites of the H, AP, and CT groups were significantly different. We observed that the Lachnospiraceae family depleted concomitant with acetoacetate and beta-hydroxybutyric acid (BHB) accumulations in the AP tissues. In addition, some bacterial species including Gemella morbillorum, and Morganella morganii were enriched in the AP compared to the H group. Furthermore, fumarate was accumulated concomitant to Aeromonas enteropelogenes, Aeromonas veronii, and Fusobacterium nucleatum subsp. animalis increased abundance in the CT compared to the H group. Conclusion These results proposed that beneficial bacteria including the Lachnospiraceae family depletion cross-talk with acetoacetate and BHB accumulations followed by an increased abundance of driver bacteria including G. morbillorum, and M. morganii may reprogram polyp microenvironment leading to tumor initiation. Consequently, passenger bacteria accumulation like A. enteropelogenes, A.veronii, and F. nucleatum subsp. animalis cross-talking fumarate in the TME may aggravate cancer development. So, knowledge of TME bacteriome and metabolites might help in cancer prevention, early diagnosis, and a good prognosis.